Accustoming a new everyday life. On the cultural adaptation and integration of the borderland people in Opole Silesia - Sitnik, Tomasz (Studia Etnologiczne i Antropologiczne, 2012)
The author makes an attempt to culturally analyse the Upper-Silesian mosaic formed after the World War II. As a result of political arrangements, the line of the already-existing borders of Poland changed. The effect of these “shifts” was mass and forced relocations of Polish people from the Eastern borderlands of the Second Republic of Poland to the West, the so called regained lands, as well as forcing Germans to go outside the western border. At the same time, Opole Silesia, among others, became the arena of dramatic changes in 1945. A radical violation of the everyday reality happened here. The settlers from the east deprived of almost all material and spirituals values came there. The Silesians who did not leave their small homeland also found themselves in this socio-cultural setting. It turned out that these two ethnic groups have to somehow re-work out their joint everyday life, and assimilate different cultural patterns. The very process underwent big hardships due to a fairly often and strong opposition of both groups. Everyday differences, discerned almost immediately, such as clothing, food or language additionally made the process of adaptation and integration complex, as well as brought about conflict-rising situations. The element having a negative influence on intergroup relations and facilitating stereotype generation was also beliefs and rightness of both groups, e.g. the borderlanders looked for a kind of compensation for damages experiences during the war in this new reality. A cultural integration seemed possible, as it seems, when the oldest generation of passed away, who cherished the borderland traditions to a large extent. Their descendants, born in Opole Silesia treat the land of their ancestors in a different way as it is simply foreign to them. An early stage of socialization (e.g. kindergarten or school) seems to be a factor facilitating the process of integration teaching tolerance towards a multicoloured Silesian everyday life.